Evaluación de tres marcas comerciales de packs reproductivos para IATF en ganado de carne cruza cebú - Prieto, Paula Noelia; Etchepare, Paulo; Bordón, Ángel; Vispo, Pablo Esteban; Helguero, Pedro Santiago; Stahringer, Rodolfo Carlos (AAPA, 2022)
Póster